Negative active material and preparation method thereof, negative pole piece and secondary battery

The preparation of sodium-rich lithium titanate materials through hydrothermal method solves the low efficiency and performance problems of hard carbon materials in sodium ion batteries, and achieves the efficient electrochemical performance and long life of sodium ion batteries.

CN119503866APending Publication Date: 2025-02-25LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411660672.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Hard carbon, as an anode material for sodium ion batteries, has low first-circuit Coulomb efficiency, relatively poor magnification and cycling performance, which affects its commercialization process.

Method used

Sodium-rich lithium titanate material (NLTO) was prepared by hydrothermal method. By mixing and reacting titanium source, lithium source, sodium source, alkaline substance and transition metal source in solvent, the particle size of the product was adjusted to be between 30 and 220 nm, and sintering was performed to obtain the negative electrode active material.

Benefits of technology

The excellent electrochemical performance of sodium ion batteries is achieved, including high first-time Coulomb efficiency, good rate performance and long cycle life, reducing the risk of thermal runaway and improving the thermal stability and self-discharge performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a negative active material and a preparation method thereof, a negative pole piece and a secondary battery. The preparation method comprises the following steps: S1, mixing and reacting a titanium source and a lithium source in a solvent, and regulating D50 of a product to be 30-220 nm; and S2, mixing the product with a sodium source, and sintering to obtain the sodium-rich lithium titanate material. According to the method, a hydrothermal method is utilized, a lithium source and a titanium source are taken as raw materials, a pure-phase nano material with uniform size can be obtained, a material synthesis process which cannot be completed under normal pressure can be realized, and the method is a potential method for obtaining the high-performance sodium-rich lithium titanate material. Compared with the prior art, the defects of a solid phase method in synthesis of sodium lithium titanate, such as obvious increase of the particle size of the material under high-temperature calcination, high energy consumption in the reaction process, generation of other impurities and the like, are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode active material and a preparation method thereof, a negative electrode plate, and a secondary battery. Background Art

[0002] Due to the small amount of lithium in the natural environment, uneven distribution and high price, lithium-ion batteries using lithium as raw materials are in sharp contrast with sodium-ion batteries, which are abundant in resources and cheap. Similar to the graphite negative electrode used in commercial lithium-ion batteries, carbon-based negative electrode materials with low reactivity and high safety are also the mainstream negative electrode materials for commercial sodium-ion batteries, mainly composed of graphite materials, soft carbon materials and hard carbon materials.

[0003] For graphite-based negative electrode materials, although their theoretical lithium storage capacity is as high as 372 mAh g -1 , but its sodium storage capacity is extremely poor, with a capacity of only 12 mAh·g -1 In contrast, soft carbon and hard carbon with amorphous structure have higher sodium storage reversible capacity (200 mAh g -1 Up to 400 mAh g -1 range) and better cycle performance, and is expected to be commercialized after controlling costs.

[0004] Asphalt, resin, coal, etc. can all be used to prepare hard carbon and soft carbon after pretreatment, indicating that the structural composition of the two is similar, consisting of graphite nanocrystals and amorphous regions. However, compared with soft carbon, the carbon layer structure of hard carbon materials is disordered and cross-linked, and the layered structure is underdeveloped, making its structure more stable at high temperatures. In addition, the interlayer spacing of hard carbon materials is larger than that of soft carbon materials, and there are more active sites, which is conducive to further improvement of sodium storage capacity. In summary, hard carbon is currently the most suitable carbon-based material for the negative electrode of sodium-ion batteries.

[0005] However, as the most promising sodium ion negative electrode material, hard carbon still has problems such as low first-cycle coulombic efficiency, relatively poor rate and cycle performance, which have a great impact on its commercialization process.

[0006] At present, P2-type titanium-based layered oxide materials with titanium ions as central atoms exhibit high structural stability, which is due to the tetravalent structure of titanium ions that is stable to air. However, the electrochemical decomposition reaction of layered oxides is violent under high pressure, which seriously affects the actual commercial application of layered oxide materials. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a negative electrode active material and a preparation method thereof, a negative electrode sheet, and a secondary battery. The negative electrode active material is used as a negative electrode material of a sodium-containing secondary battery, which can make the sodium ion battery have excellent electrochemical properties.

[0008] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a negative electrode active material, comprising the following steps: S1: After mixing a titanium source, a lithium source, an optional sodium source, an optional alkaline substance and an optional transition metal source in a solvent and reacting them, the D of the product is adjusted. 50 At 30~220 nm; S2: The product is mixed with an optional sodium source and then sintered to obtain a negative electrode active material.

[0009] In the present invention, the negative electrode active material is a sodium-rich lithium titanate material (abbreviated as NLTO).

[0010] Preferably, the mass ratio of the titanium source, lithium source, sodium source, alkaline substance and transition metal source is (1-100):1:(0-1):(0-10):(0-0.1).

[0011] Preferably, the D of the regulated product 50 At 30-220 nm, this can be achieved by any one or more of the following methods (1) to (3): Method (1): Mixing a mixture of a titanium source, a lithium source, an optional alkaline substance, an optional transition metal source and a solvent with any one or more of glycerol, C12-C30 glycerides, C12-C30 saturated fatty acids, and C12-C30 unsaturated fatty acids; Method (2): subjecting a mixture of a titanium source, a lithium source, a sodium source, an alkaline substance, an optional transition metal source and a solvent to electrospinning; Method (3): A mixture of a titanium source, a lithium source, an optional alkaline substance, an optional transition metal source and a solvent is subjected to ultrasonic treatment.

[0012] Preferably, the titanium source is selected from any one or more of n-butyl titanate, iron titanate, rutile or titanium dioxide.

[0013] Preferably, the lithium source is selected from any one or more of lithium hydroxide, lithium carbonate, n-butyl lithium or lithium acetate.

[0014] Preferably, the sodium source is selected from any one or more of sodium oxide, sodium peroxide, sodium carbonate and sodium acetate.

[0015] Preferably, the solvent is selected from any one or more of acetic acid, alcohol reagents, acetonitrile, acetone or pyrrolidone.

[0016] Preferably, the transition metal source is selected from any one or more of transition metal-containing acetates, transition metal-containing alkoxides or transition metal-containing hydroxides; the transition metal is selected from any one or more of titanium, cobalt, nickel, iron, manganese or lanthanum.

[0017] Preferably, the sintering further comprises the following steps: The product is blended with a carbon source, treated at high temperature, and then mixed with an optional sodium source.

[0018] Preferably, the high temperature treatment is carried out under ultrasonic conditions.

[0019] Preferably, the high temperature treatment is carried out at a temperature of 180-250° C., a pressure of 0.1-0.3 GPa, and a time of 20-30 h.

[0020] Preferably, the carbon source is selected from any one or more of glucose, asphalt, citric acid, graphene, o-phenanthroline or polyvinyl pyrrolidone.

[0021] Preferably, the mass ratio of the titanium source to the carbon source is 1:(0~0.1).

[0022] Preferably, the reaction temperature is 100-240° C., and the reaction pressure is 1 MPa-1 Gpa.

[0023] Preferably, the sintering temperature is 400-2000° C., and the sintering time is 4-12 h.

[0024] In a second aspect, the present invention further provides a negative electrode active material prepared by the above preparation method, wherein the size of the negative electrode active material is 30-220 nm.

[0025] In a third aspect, the present invention further provides a negative electrode plate, comprising a binder, a conductive agent and the above-mentioned negative electrode active material.

[0026] Preferably, the conductive agent is selected from conductive carbon black.

[0027] Preferably, the binder is selected from polyvinylidene fluoride.

[0028] Preferably, the mass ratio of the binder, the conductive agent and the negative electrode active material is (1-10):(1-20):(80-100).

[0029] In a fourth aspect, the present invention provides a secondary battery comprising the above-mentioned negative electrode plate.

[0030] Preferably, the secondary battery includes any one of a sodium-sulfur battery, a sodium-ion battery or a sodium metal battery.

[0031] Preferably, the type of the secondary battery is selected from any one of a button battery, a soft pack battery, a square battery, a steel shell battery, an aluminum shell battery or a 18650 battery.

[0032] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a negative electrode active material, namely, a sodium-rich lithium titanate material. The method utilizes a hydrothermal method, uses a lithium source and a titanium source as raw materials, can obtain a pure phase, uniform-sized nanomaterial, and can achieve a material synthesis process that cannot be completed under normal pressure, and is a method with great potential for obtaining high-performance sodium-rich lithium titanate materials. Compared with the prior art, the method avoids the defects of the solid phase method in synthesizing sodium lithium titanate, such as the significant increase in the particle size of the material under high-temperature calcination, and the large energy consumption and generation of other impurities during the reaction process.

[0033] Since the sodium-rich lithium titanate material is nano-sized, the ion diffusion distance can be shortened to improve the performance of the material. In addition, the sodium-rich lithium titanate material has a zero strain characteristic. In actual application, during repeated charging and discharging, no stress is generated inside the lithium titanate particles, avoiding problems such as particle breakage and structural collapse caused by volume expansion and contraction, and significantly improving the cycle life of the battery. At the same time, the lack of significant volume change reduces the heat generation caused by the release of internal stress, reduces the risk of thermal runaway, and makes the sodium-rich lithium titanate-based sodium battery have better thermal stability. It can also ensure that the contact resistance between the electrode and the current collector is stable, which is beneficial to electron transmission and improves the overall battery performance. Furthermore, the sodium-rich lithium titanate material has a fixed crystal structure, which helps to reduce the instability of its contact interface with the electrolyte, reduce the occurrence of side reactions, and further improve the self-discharge performance of the battery.

[0034] The sodium-rich lithium titanate in the present invention, as a spinel structure phase with lithium titanate as the core, has a more stable central ion support structure, that is, better high-pressure decomposition stability, compared with titanium-based layered oxide materials. At the same time, the sodium storage capacity under this structure is significantly increased, and the material structure after sodium storage is more stable, and has higher electrochemical stability. At the same time, the sodium-rich lithium titanate with lithium titanate as the core can be directly applied to the synthesis production line of lithium titanate, making its synthesis process simple, and can draw on the experience of lithium titanate synthesis, which has great inherent advantages for enterprises to control quality control and reduce production equipment costs.

[0035] After testing, the sodium ion battery using the sodium-rich lithium titanate material of the present invention as the negative electrode material and sodium vanadium fluorophosphate as the positive electrode material can achieve an initial coulombic efficiency of more than 90%, a first-cycle discharge capacity of more than 145 mAh / g, a 1C-300 cycle capacity retention rate of more than 94%, and a 1C-500 cycle capacity retention rate of more than 85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a SEM image of the sodium-rich lithium titanate material obtained in Example 1; Figure 2 This is the SEM image of the sodium lithium titanate material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Based on the problems existing in the prior art of carbon-based sodium ion battery negative electrode materials, the present invention proposes a negative electrode active material and a preparation method and application thereof, specifically a new modified sodium titanate-rich lithium 6 LiTi 5 O 12 ) Negative electrode material and its preparation method, as well as its application in negative electrode sodium storage of sodium ion battery.

[0039] Lithium Titanate (LTO) and LiMn 2 O 4 The structure is similar, belonging to the spinel structure, and is a white non-conductive crystal. 4 Ti 5 O 12 The unit cell is composed of 32 O 2- The FCC face-centered cubic lattice, O 2- All of them are occupied at the 32e position, and the 8a position in the tetrahedral gap is occupied by 75% of Li + All of them, while the other 25% of Li + Then and Ti 4+ Together they occupy the 16d position in the octahedral gap, and their structural formula can be written as [Li] 8a [Li 1 / 3 Ti 5 / 3 ] 16d [O 12 ] 32e , the lattice constant a is between 0.835~0.837 nm.

[0040] As a "zero strain" material, spinel lithium titanate is widely used in lithium-ion batteries. During the intercalation and deintercalation, the volume change is less than 1%, which can be ignored. This is the most important characteristic of lithium titanate. The three-dimensional octahedral network spinel structure of lithium titanate is highly symmetrical. Each lithium ion is located in the tetrahedral void formed by oxygen atoms, which can form a stable Li-O bond. This tightly ordered crystal structure gives lithium titanate good mechanical stability. At the same time, the strength of the Ti-O bond in lithium titanate is extremely high, and the Ti-O bond is not easy to break during the intercalation and deintercalation of lithium ions and sodium ions, so that its structure remains stable and the volume change is not obvious. During the charge and discharge process, the migration of lithium ions in lithium titanate is not through a solid-state diffusion mechanism, but through surface reactions (surface adsorption-desorption process). Specifically, when the battery is charging, lithium ions are released from the positive electrode and migrate to the surface of the negative electrode of lithium titanate, and react with Ti4 + Ions combine to form LiTiO 2 During discharge, lithium ions are transported from the surface LiTiO 2 Since most of the insertion and extraction of lithium ions occur on the surface of the crystal rather than deep inside the crystal, the volume of lithium titanate hardly changes during the entire charging and discharging process.

[0041] However, when lithium titanate is used in sodium ion batteries, the volume of lithium titanate changes by about 13% during the process of sodium insertion and removal, resulting in capacity decay. Therefore, the present invention has modified the basic lithium titanate material by blending. The sodium storage mechanism of lithium titanate belongs to the three-phase separation mechanism: that is, during the discharge process, sodium ions will specifically occupy the 16c site to form Na 6 Li, at the same time, Li 8a The ions are pushed toward the nearby Li 4 phase to form Li 7 phase, forming three-phase coexistence, and the following reaction occurs: 2Li 4 Ti 5 O 12 +6Na+6e - →Li 7 Ti 5 O 12 +Na 6 LiTi 5 O 12 .

[0042] The sodium storage product of spinel lithium titanate is lithium sodium titanate, which has the characteristics of good cycle performance, high safety, high mass production reliability, excellent sodium storage capacity, and relatively high redox potential. It is considered to be a sodium ion battery negative electrode material with commercial application prospects.

[0043] However, the prior art generally adopts a solid phase method to prepare sodium lithium titanate, which has the problems of large particle size, easy generation of impurities and high energy consumption. Based on this, the present invention provides a method for preparing a negative electrode active material, that is, a sodium-rich lithium titanate material, comprising the following steps: S1: After mixing a titanium source, a lithium source, an optional sodium source, an optional alkaline substance and an optional transition metal source in a solvent and reacting them, the D of the product is adjusted. 50 At 30~220 nm; S2: mixing the product with an optional sodium source and sintering the mixture to obtain a sodium-rich lithium titanate material; The sodium source in step S1 and in step S2 are not present at the same time.

[0044] It should be noted that the "optional" mentioned in the above "optional sodium source, optional alkaline substance, and optional transition metal source" means that it can be added or not. Adjustments can be made for different technical solutions. The mass ratio of the titanium source, lithium source, sodium source, alkaline substance and transition metal source is (1-100):1:(0-1):(0-10):(0-0.1), preferably (1-95):1:(0.1-1):(1-10):(0.02-0.1).

[0045] The present invention adopts a hydrothermal method, firstly, a titanium source, a lithium source, an optional sodium source, an optional alkaline substance and an optional transition metal source are mixed and reacted in a solvent, and the size of the product is regulated to be 30-220 nm, so as to ensure that when it is used as an electrode material in the future, the particle size can meet the three-phase diffusion conditions of sodium ions and realize the sodium storage function. Then, the product is mixed with an optional sodium source and sintered to obtain a sodium-rich lithium titanate material.

[0046] Among them, the titanium source is selected from any one or more of n-butyl titanate, iron titanate, rutile or titanium dioxide; the lithium source is selected from any one or more of lithium hydroxide, lithium carbonate, n-butyl lithium or lithium acetate; the sodium source is selected from any one or more of sodium oxide, sodium peroxide, sodium carbonate, sodium acetate, preferably sodium oxide; the solvent is selected from any one or more of acetic acid, alcohol reagents, acetonitrile, acetone or pyrrolidone, and the alcohol reagent is preferably ethanol; the transition metal source is selected from any one or more of acetates containing transition metals, alkoxides containing transition metals or hydroxides containing transition metals; the transition metal is selected from any one or more of titanium, cobalt, nickel, iron, manganese or lanthanum; to avoid introducing other impurity ions, the cation of the alkaline substance is selected from sodium or lithium, and the anion is generally consistent with the anion of the solvent. In some embodiments of the present invention, the alkaline substance can be specifically selected from any one or more of lithium hydroxide, sodium hydroxide, sodium alkoxide or sodium acetate, which not only has alkalinity, but can also be used as a sodium source or a lithium source. The present invention has no particular limitation on the sources of the titanium source, lithium source, sodium source, alkaline substance, transition metal source and solvent, and they may be generally commercially available products.

[0047] In the present invention, the D of the regulated product 50 At 30-220 nm, this can be achieved by any one of the following methods (1) to (3) or a combination of any two or more: Method (1): Mixing a mixture of a titanium source, a lithium source, an optional alkaline substance, an optional transition metal source and a solvent with any one or more of glycerol, C12-C30 glycerides, C12-C30 saturated fatty acids, and C12-C30 unsaturated fatty acids; Method (2): subjecting a mixture of a titanium source, a lithium source, an alkaline substance, an optional transition metal source and a solvent to electrospinning; or A mixture of a titanium source, a lithium source, an optional alkaline substance, an optional transition metal source, and a solvent is sonicated.

[0048] In some embodiments of the present invention, it is preferred that the titanium source and the lithium source are mixed and reacted in a solvent, and then the obtained mixture is mixed with any one or more of glycerol, C12-C30 glycerides, C12-C30 saturated fatty acids, and C12-C30 unsaturated fatty acids, preferably glycerol, and the amount of glycerol added is controlled to control the D 50It is 30~220 nm. It should be noted that after adding glycerol, the product obtained is a nanorod structure, and the size is the diameter of the cross section of the nanorod. The mass ratio of the titanium source and the lithium source is (1~100):1, preferably (5~80):1, and more preferably (10~60):1. The reaction temperature is 100~240°C, preferably 120~200°C; the reaction pressure is 1 MPa~1 Gpa, preferably 0.1~0.8 Gpa.

[0049] After the reaction is completed, the obtained product is preferably sintered with a sodium source to obtain a sodium-rich lithium titanate material. As a preferred technical solution, after the above reaction is completed, the product is post-treated, and the post-treatment includes but is not limited to washing and drying, and then sintered with a sodium source.

[0050] The sintering temperature is 400-2000°C, preferably 650-850°C; the sintering time is 4-12 h, preferably 8-10 h. The mass ratio of the titanium source to the sodium source is (1-100):(0.1-1), preferably (5-80):(0.3-0.8).

[0051] In other embodiments of the present invention, it is preferred to mix the titanium source and the lithium source in a solvent and react them, and then perform ultrasonic treatment to control the D 50 The ultrasonic wave has a power of 70 to 1000 W, preferably 100 to 800 W, and a time of 5 to 12 h, preferably 6 to 8 h.

[0052] It should be noted that other ions such as Mo, K, Na, Gd, Sc, Sm, Ni, F, PO 4 3- Plasma can effectively improve the rate performance of lithium sodium titanate. According to the ion and charge compensation mechanism, part of the Ti 4+ Transformed into Ti 3+ , improve Ti 3+ / Ti 4+ The ratio of ions to lithium titanate increases the electron concentration, thereby improving the conductivity of lithium titanate. + 、Ti 4+ and O 2- , which can effectively improve the kinetic coefficient of the material and improve the rate performance of lithium sodium titanate.

[0053] Therefore, in some preferred embodiments of the present invention, the titanium source, lithium source, alkaline substance and transition metal source can be mixed, and then the size of the product can be adjusted by method (1) or method (3). Then sintering is performed. The sintering can refer to the relevant content in the above technical solution.

[0054] It should be noted that other ions such as Mo, K, Na, Gd, Sc, Sm, Ni, F, PO 4 3- Plasma can effectively improve the rate performance of lithium sodium titanate. According to the ion and charge compensation mechanism, part of the Ti 4+ Transformed into Ti 3+ , improve Ti 3+ / Ti 4+ The ratio of ions to lithium titanate increases the electron concentration, thereby improving the conductivity of lithium titanate. + 、Ti 4+ and O 2- , which can effectively improve the kinetic coefficient of the material and improve the rate performance of lithium sodium titanate.

[0055] In some specific embodiments of the present invention, it is preferred that after the titanium source, lithium source, alkaline substance and transition metal source are mixed in a solvent and reacted, the D of the product is regulated by method (1) or method (3). 50 The alkaline substance is specifically selected from any one or more of sodium acetate, sodium hydroxide or sodium alcoholate. In order to avoid interference caused by the introduction of unnecessary anions, it is preferred that the anions in the alkaline substance are consistent with the anions in the solvent. For example, if acetic acid is selected as the solvent, sodium acetate is selected as the alkaline substance. The transition metal in the transition metal source can replace a small amount of Li + 、Ti 4+ and O 2- , improve the rate performance of the material, the transition metal source is selected from any one or more of transition metal-containing acetates, transition metal-containing alkoxides or transition metal-containing hydroxides; the transition metal is selected from any one or more of titanium, cobalt, nickel, iron, manganese or lanthanum, preferably lanthanum. It should be noted that the anions in the transition metal source are preferably consistent with the anions of the alkaline substance. In the present invention, the mass ratio of the titanium source, lithium source, alkaline substance and transition metal source is (1~100):1:(1~10):(0~0.1), preferably (5~80):1:(2~8):(0.02~0.08), and more preferably (10~60):1:(3~5):(0.05~0.06). The reaction temperature is 100~240°C, preferably 120~200°C; the reaction pressure is 1 MPa~1 Gpa, preferably 0.1~0.8 Gpa. Then sintering is performed. The sintering can refer to the relevant content in the above technical solution.

[0056] It should be noted that in the present invention, the D of the product is regulated by method (2). 50At 30-220 nm, a mixture of a titanium source, a lithium source, a sodium source, an alkaline substance, an optional transition metal source and a solvent is preferably subjected to electrospinning. Specifically, in some embodiments of the present invention, the titanium source, the lithium source and the transition metal source are preferably mixed in proportion and uniformly dispersed in a solvent; the reaction temperature is set to 100-240°C and the pressure is 1 MPa-1 Gpa; the sodium source is added to the mixed solution, and a precursor fiber bundle is prepared by electrospinning technology; the precursor fiber bundle is then sintered to obtain a transition metal ion-substituted sodium lithium titanate fiber material.

[0057] In some preferred embodiments of the present invention, after the obtained product is mixed with a carbon source, the product is further ultrasonicated at 100-240°C and 1 MPa-1 Gpa for 15-30 h, preferably 18-24 h. The carbon source is selected from any one or more of glucose, asphalt, citric acid, graphene, o-phenanthroline or polyvinyl pyrrolidone; the mass ratio of the titanium source to the carbon source is 1:(0-0.1), preferably 1:(0.01-0.05), and more preferably 1:0.02. The obtained product is then mixed with an optional sodium source (for methods (1) and (3), sintered after mixing with a sodium salt; for method (2), directly sintered), and sintered. For the specific parameters of sintering, refer to the above technical solution.

[0058] In the present invention, the addition of the above carbon source can optimize the subsequent electronic conductivity after the electrode is prepared, and improve the electrochemical performance and cycle life of the battery.

[0059] The present invention also provides a sodium-rich lithium titanate material prepared according to the above preparation method, wherein D of the sodium-rich lithium titanate material is 50 The size is 30~220 nm.

[0060] In some preferred embodiments of the present invention, the sintered product is preferably dried and then subjected to a series of processes to obtain a negative electrode sheet.

[0061] Based on this, the present invention also provides a sodium-rich lithium titanate negative electrode plate, which includes a binder, a conductive agent and a sodium-rich lithium titanate material. The conductive agent is selected from conductive carbon black; the binder is selected from polyvinylidene fluoride. The mass ratio of the binder, the conductive agent and the sodium-rich lithium titanate material is (1-10): (1-20): (80-100), preferably (2-4): (3-10): (86-95).

[0062] The sodium-rich lithium titanate negative electrode plate can be prepared according to the standard preparation method in the industry and is not particularly limited here.

[0063] The present invention also provides a secondary battery, which comprises the above-mentioned sodium-rich lithium titanate negative electrode plate.

[0064] The secondary battery includes any one of a sodium-sulfur battery, a sodium-ion battery or a sodium metal battery, and the positive electrode materials in different batteries can be adjusted according to actual needs.

[0065] The type of the secondary battery is selected from any one of button batteries, soft-pack batteries, square batteries, steel-shell batteries, aluminum-shell batteries or 18650 batteries.

[0066] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0067] Example 1

[0068] This embodiment provides a sodium lithium titanate nanoparticle, and the preparation method thereof comprises the following steps: (1) n-butyl titanate / lithium acetate were mixed in a mass ratio of 3:1, dissolved in a 90% ethanol / pyrrolidone solution and uniformly dispersed; (2) Set the reaction temperature to 200 °C and the reaction pressure to 10 MPa; (3) By adding 3% mass fraction of glycerol, the morphology and size of the reaction product were controlled (sampling inspection, SEM or TEM test, control of D 50 In the range of 30-220 nm, (the SEM images of the obtained products are shown in Figure 1 shown); (4) drying the reaction product, mixing with 3% by mass of sodium oxide and sintering at 600°C; (5) The sintered product is subjected to processes such as homogenization, coating, rolling, drying, and lamination to obtain a negative electrode sheet.

[0069] Battery Assembly: The electrolyte is commercial EC / DMC / LIPF6 commercial electrolyte, the diaphragm is commercial PP diaphragm, and the positive electrode is commercial sodium vanadium fluorophosphate; The negative electrode material is prepared by methods well known to those skilled in the art, wherein the ratio of negative electrode sheet: binder (polyvinylidene fluoride): conductive agent (carbon black) is 86:4:10.

[0070] Example 2 This embodiment provides a sodium lithium titanate nanoparticle, and the preparation method thereof comprises the following steps: (1) n-butyl titanate / lithium hydroxide / copper sulfate are mixed in a mass ratio of 4.5:2:0.05, dissolved in a 3% acetic acid solution and uniformly dispersed; the lithium hydroxide is used as a lithium source and an alkaline substance at the same time; (2) Set the reaction temperature to 220°C and the reaction pressure to 3 MPa; (3) 1% by mass of sodium acetate was added to the mixed solution, and a precursor fiber bundle was prepared by electrospinning technology; (4) sintering the obtained fiber bundle in an argon atmosphere to obtain a copper ion-substituted sodium lithium titanate fiber material; (5) Drying the reaction product and obtaining the negative electrode sheet through processes such as slurrying, coating, rolling, drying, and lamination.

[0071] A sodium ion battery was prepared according to Example 1.

[0072] Example 3 This embodiment provides a modified sodium lithium titanate nanoparticle, and the preparation method thereof comprises the following steps: (1) n-butyl titanate / lithium hydroxide / lanthanum sulfate are mixed in a mass ratio of 3:2:0.04, dissolved in a 3% acetic acid solution and uniformly dispersed; the lithium hydroxide is used as a lithium source and an alkaline substance at the same time; (2) Set the reaction temperature to 150°C and the reaction pressure to 10 MPa; (3) 1% by mass of sodium acetate was added to the mixed solution, and a precursor fiber bundle was prepared by electrospinning technology; (4) sintering the obtained fiber bundle in an argon atmosphere to obtain a lanthanum ion-substituted sodium lithium titanate fiber material; (5) Drying the reaction product and obtaining the negative electrode sheet through processes such as slurrying, coating, rolling, drying, and lamination.

[0073] A sodium ion battery was prepared according to Example 1.

[0074] Example 4 This embodiment provides a modified sodium lithium titanate nanoparticle, and the preparation method thereof comprises the following steps: (1) Tetrabutyl titanate / n-butyl lithium were mixed in a mass ratio of 3:1, dissolved in 3% acetic acid solution and uniformly dispersed; (2) Set the reaction temperature to 100 °C and the reaction pressure to 1 MPa; perform ultrasonic reaction for 6 hours; (3) adding 2% o-phenanthroline as a carbon source for blending; (4) Setting the reaction temperature to 240 °C and the reaction pressure to 3 MPa, and performing ultrasonic reaction for 24 hours; (5) adding 5% sodium oxide to the obtained product and calcining it at 800°C to finally obtain a carbon-coated sodium-rich lithium titanate material; (6) Drying the reaction product and obtaining the negative electrode sheet through processes such as homogenization, coating, rolling, drying, and lamination; A sodium ion battery was prepared according to Example 1.

[0075] Example 5 This embodiment provides a modified sodium lithium titanate nanoparticle, and the preparation method thereof comprises the following steps: (1) Tetrabutyl titanate / lithium hydroxide were mixed in a mass ratio of 1:1, dissolved in 3% acetic acid solution and uniformly dispersed; (2) Setting the reaction temperature to 180°C and the reaction pressure to 7 MPa; performing ultrasonic reaction for 6 hours; (3) adding 2% graphene as a carbon source for blending; (4) setting the reaction temperature to 200 °C and the reaction pressure to 0.1 GPa, and performing ultrasonic reaction for 24 hours; (5) adding 4% sodium oxide to the obtained product and calcining it at 800°C to finally obtain a carbon-coated sodium-rich lithium titanate material; (6) Drying the reaction product and obtaining the negative electrode sheet through processes such as slurrying, coating, rolling, drying, and lamination.

[0076] A sodium ion battery was prepared according to Example 1.

[0077] Comparative Example 1 This comparative example provides a commercially available micron-sized sodium lithium titanate powder (purchased from Shanghai Aladdin Technology Co., Ltd.) (its SEM image is as follows: Figure 2 as shown).

[0078] The LTO powder is subjected to processes such as homogenization, coating, rolling, drying, and lamination to obtain a negative electrode sheet; A sodium ion battery was prepared according to Example 1.

[0079] Comparative Example 2 This comparative example adopts a high temperature solid phase method to synthesize micron-sized sodium lithium titanate powder, comprising the following steps: (1) Anatase titanium dioxide, lithium carbonate and sodium carbonate were uniformly mixed in a mass ratio of 1:1:2, and urea and isopropanol were added as ball milling agents for 4 hours; (2) sintering the ball-milled slurry at 1200°C for 24 hours; (3) The sodium lithium titanate powder obtained in the above step is ball-milled again.

[0080] A sodium ion battery was prepared according to Example 1.

[0081] The sodium ion batteries obtained in the examples and comparative examples were characterized by using Wuhan Blue Electric Tester for long cycle discharge specific capacity, first efficiency, capacity retention rate and other electrical properties. The results are shown in Table 1 below: Table 1

[0082] The above-mentioned Example 1 is a nano-sized sodium lithium titanate prepared by a hydrothermal method; Examples 2-3 are based on the preparation of nano-sized sodium lithium titanate by a hydrothermal method, and transition metals are doped to replace part of the lithium; Examples 4-5 are based on the preparation of nano-sized sodium lithium titanate by a hydrothermal method, and carbon coating is further performed.

[0083] It can be seen from the data in Table 1 that the products obtained in Examples 1 to 5 can all be used as negative electrode materials to make sodium ion batteries have excellent electrochemical properties. Among them, the nanoscale lithium sodium titanate prepared by the hydrothermal method and the solid phase method has great advantages in rate performance when used. The micron-scale NLTO powder and the nanoscale NLTO powder have a greater influence on the diffusion reaction of sodium ions, which is reflected in the capacity retention rate and rate performance of long cycles as a whole. Furthermore, the present invention designs the size of NLTO powder, blends transition metal ions and carbon-coates it, which can further improve the sodium storage performance of the lithium titanate negative electrode.

[0084] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a negative electrode active material, characterized in that: The following steps are involved: S1: After mixing a titanium source, a lithium source, an optional sodium source, an optional alkaline substance and an optional transition metal source in a solvent and reacting them, the D of the product is adjusted. 50 At 30~220 nm; S2: The product is mixed with an optional sodium source and then sintered to obtain a negative electrode active material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the titanium source, lithium source, sodium source, alkaline substance and transition metal source is (1-100):1:(0-1):(0-10):(0-0.1).

3. The preparation method according to claim 1 or 2, characterized in that: The D of the regulated product 50 At 30-220 nm, this can be achieved by any one or more of the following methods (1) to (3): Method (1): Mixing a mixture of a titanium source, a lithium source, an optional alkaline substance, an optional transition metal source and a solvent with any one or more of glycerol, C12-C30 glycerides, C12-C30 saturated fatty acids, and C12-C30 unsaturated fatty acids; Method (2): subjecting a mixture of a titanium source, a lithium source, a sodium source, an alkaline substance, an optional transition metal source and a solvent to electrospinning; Method (3): A mixture of a titanium source, a lithium source, an optional alkaline substance, an optional transition metal source and a solvent is subjected to ultrasonic treatment.

4. The preparation method according to any one of claims 1 to 3, characterized in that The titanium source is selected from any one or more of n-butyl titanate, iron titanate, rutile or titanium dioxide; The lithium source is selected from any one or more of lithium hydroxide, lithium carbonate, n-butyl lithium or lithium acetate; The sodium source is selected from any one or more of sodium oxide, sodium peroxide, sodium carbonate, and sodium acetate; The solvent is selected from any one or more of acetic acid, alcohol reagents, acetonitrile, acetone or pyrrolidone; The transition metal source is selected from any one or more of transition metal-containing acetates, transition metal-containing alkoxides or transition metal-containing hydroxides; the transition metal is selected from any one or more of titanium, cobalt, nickel, iron, manganese or lanthanum.

5. The preparation method according to any one of claims 1 to 4, characterized in that The sintering process also includes the following steps: The product is mixed with a carbon source, treated at high temperature, and then mixed with an optional sodium source; The high temperature treatment is carried out under ultrasonic conditions; The high temperature treatment is performed at a temperature of 180-250° C., a pressure of 1-1000 Mpa, and a time of 20-30 h.

6. The preparation method according to claim 5, characterized in that: The carbon source is selected from any one or more of glucose, asphalt, citric acid, graphene, o-phenanthroline or polyvinyl pyrrolidone; The mass ratio of the titanium source to the carbon source is 1:(0~0.1).

7. The preparation method according to any one of claims 1 to 6, characterized in that The reaction temperature is 100-240°C, and the reaction pressure is 1 MPa-1 Gpa; The sintering temperature is 400-2000° C., and the sintering time is 4-12 h.

8. The negative electrode active material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The size of the negative electrode active material is 30-220 nm.

9. A negative electrode plate, characterized in that: The invention comprises a binder, a conductive agent and a negative electrode active material prepared by the preparation method according to any one of claims 1 to 7.

10. The negative electrode sheet according to claim 9, characterized in that: The conductive agent is selected from conductive carbon black; The binder is selected from polyvinylidene fluoride.

11. The negative electrode sheet according to claim 9 or 102, characterized in that: The mass ratio of the binder, the conductive agent and the negative electrode active material is (1-10):(1-20):(80-100).

12. A secondary battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 9 to 12.

13. The secondary battery according to claim 12, characterized in that: The secondary battery comprises any one of a sodium-sulfur battery, a sodium-ion battery or a sodium metal battery; The type of the secondary battery is selected from any one of button batteries, soft-pack batteries, square batteries, steel-shell batteries, aluminum-shell batteries or 18650 batteries.